Profesionalitas Guru Akidah Akhlak yang Berdampak Pada Pembinaan Akhlak Siswi di Madrasah Tsanawiyah Hidayatul Mubtadiin Putri Tegalgubug - J, Jumriyah; M, Mujahid; Abduloh Nuh, Muhammad; Nadawah, Zaimatun; Ali, Abdul Muiz (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Research background found a female student in Mts HM whose morals were only based on intention, for example, when someone is in trouble, the student often ignores them, which does not make morals a foundation and reference. This study aims to determine the professionalism of Akidah Akhlak teachers, the impact of the professionalism of Akidah Akhlak teachers on the guidance of female students' morals, supporting factors and obstacles to the guidance of female students' morals in MtsHM. This is a qualitative descriptive research method. Data collection is done through observation techniques, interviews, and documentation, as well as interviews with the vice principal, Akidah Akhlak teachers, and 3 female students. Then the researcher directly goes into the field. Data analysis techniques used are data reduction, data display, and conclusion drawing. The results showed that the professionalism of Akidah Akhlak teachers in MtsHM is already included in professional teachers. The impact of teachers in guiding morals is teaching students to help each other. The inhibiting and supporting factors of moral guidance are environmental factors.